The global spread of Islamism and the consequences for terrorism - Freeman, Michael (University of Nebraska Press, 2021)
The Supply of an Ideology -- Exporting Islamism -- Islamism in Indonesia -- Islamism in Pakistan -- Islamism in Britain -- Islamism in the United States -- Countering an Ideology.